Fatigue Life Analysis of Harmonic Reducer Flexspline based on Cold Rolling Process - Wu Shangsheng; Sun Hanlei; Yang Qi (Jixie chuandong)
According to the inhibitory effect of initial residual stress produced by cold rolling process on crack initiation and crack propagation,taking the cold rolling flexspline of harmonic reducer as the research object,the SWT method and fracture mechanics theory are used to carry out theoretical analysis of crack initiation life and crack propagation life of cold rolling flexspline respectively,and the verification of each other is carried out by using the simulation analysis of the fatigue analysis software nCode Design-Life. The results show that the fatigue life of cold rolling flexspline are better than the machining flexspline in various stages,and the working life of the harmonic reducer is prolonged. The research results verify the advantages of cold rolling process of flexspline,and have important reference value for improving the performance of flexspline.